Knowledge, Attitudes, and Practices on Oral Health among Beneficiaries under the Pantawid Pamilyang Pilipino Program (4Ps) in Tarlac City/Kathleen Paulette S. Ong. - Ong, Kathleen Paulette S., author
Introduction: The Pantawid Pamilyang Pilipino Program (4Ps), a conditional cash transfer program in the Philippines, aims to invest on the education and health of the disadvantaged population. To receive cash grants, at least one responsible member of the household must attend the family development session (FDS), a monthly gathering on health and family life and development. At present, the program does not have an oral health component nor FDS on oral health. This study determined the knowledge, attitudes, and practices on oral health of the 4Ps beneficiaries